Pengembangan Paket Wisata di Desa Wisata Tambang Ayam Anyer: Pengabdian - Fitrianingsih, Dwi; Sucihati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service Program (PKM) aims to enhance local tourism potential through the development of tourism packages in the Tambang Ayam Tourism Village, Anyer, Serang Regency, Banten Province. Anyer is known for its high marine tourism potential, but this potential has not been optimally managed. The main problem faced by the community is the lack of integrated tourism packages that can integrate various attractions, culinary, cultural, and creative economic activities of the local community. Through this program, training, mentoring, and design of community-based tourism package models are carried out. The results of the activities show that the community is beginning to understand the concept of integrated tourism, is able to create simple tourism packages, and develops digital promotions to expand the reach of the tourism market. It is hoped that this program can become a model for sustainable empowerment in the development of tourism villages in Banten.